Web Based Home Security and Automation System - Norfadzlia Mohd Yusof; Aiman Zakwan Jidin; Lim Mei Sze (Institute of Advanced Engineering and Science, 2016)
Home security and automation is crucial issue concerned by people. A home security system is needed for convenience and safety. A home automation system is a key to having effective energy efficiency in the house. In this paper, we present the design and implementation of a web-based home security and automation system. This system make use of PIR motion sensor to detect intruder in the house. This sensor is further fed to microcontroller which would help the GSM module to send notification to house owner regarding the intrusion. On the other hand, the LDR light sensor is used to provide auto-light functionality which will turn on the light at night and dim it at day time. A web-based system function as a remote control system for user to monitor control the sensors and lights at home in order to save energy consumption. This system is accessible by user anytime and anywhere as long there is an Internet connection.